Computational reconstruction of pacemaking and intrinsic electroresponsiveness in cerebellar golgi cells - Solinas, Sergio; Forti, Lia; Cesana, Elisabetta; Mapelli, Jonathan; De Schutter, Erik; D‘Angelo, Egidio (Frontiers in Cellular Neuroscience, 2007)
The Golgi cells have been recently shown to beat regularly in vitro (Forti et al., 2006. J. Physiol. 574, 711-729). Four main currents were shown to be involved, namely a persistent sodium current (INa-p), an h current (Ih), an SK-type calcium-dependent potassium current (IK-AHP), and a slow M-like potassium current (IK-slow). These ionic currents could take part, together with others, also to different aspects of neuronal excitability like responses to depolarizing and hyperpolarizing current injection. However, the ionic mechanisms and their interactions remained largely hypothetical. In this work, we have investigated the mechanisms of Golgi cell excitability by developing a computational model. The model predicts that pacemaking is sustained by subthreshold oscillations tightly coupled to spikes. INa-p and IK-slow emerged as the critical determinants of oscillations. Ih also played a role by setting the oscillatory mechanism into the appropriate membrane potential range. IK-AHP, though taking part to the oscillation, appeared primarily involved in regulating the ISI following spikes. The combination with other currents, in particular a resurgent sodium current (INa-r) and an A-current (IK-A), allowed a precise regulation of response frequency and delay. These results provide a coherent reconstruction of the ionic mechanisms determining Golgi cell intrinsic electroresponsiveness and suggests important implications for cerebellar signal processing, which will be fully developed in a companion paper (Solinas et al., 2008. Front. Neurosci. 1:4).